Anticancer Activity of Rhizophora mucronata Leaves Extract on Sprague–Dawley Rats: In Vivo Model - Asbin Mary X; Syed Ali Mohamed Yacoob; Anuradha Venkatraman; Ruban Packiasamy; Meivelu Moovendhan; Murugesan Gnanadesigan; Yogananth Nagarajan (Journal of Toxicology)
Medicinal plants are now used to treat cancer due to the presence of bioactive compounds. Apart from the plants, mangroves also possess rich bioactive compounds with high medicinal activity. Based on the ethnobotanical attributes of Rhizophora mucronata, we are keen to work with its anticancer activity. The aim of the study is to assess the anticancer activity of methanolic extract of Rhizophora mucronata leaves against breast cancer. Its safety profile for anticancer investigations was therefore confirmed through an acute toxicity assessment. In accordance with OECD guiding principles, the study was approved to evaluate the toxicity, including acute and subacute effects and anticancer activities of methanolic extract of Rhizophora mucronata leaves on Sprague–Dawley rats. In acute toxicity trials, the dose of 1000 mg/kg body weight was determined to be safe and nontoxic even at high dose levels and did not result in any indicators of toxicity or death in the tested groups compared to controls for 14 days. In contrast, rats in a subacute toxicity study were given consistent doses of 100 mg/kg, 200 mg/kg, and 300 mg/kg for a total of 28 days along with a control group. Haematological, biochemical, and histological tests conducted in advance revealed that methanolic extract of Rhizophora mucronata leaves (MERML) at repeated doses of 200 mg/kg and 300 mg/kg was normal and had no significant effects on the treated groups. Rhizophora mucronata extract (250 mg/kg) was successfully used in in vivo trials to stop the growth of breast cancer cells in groups that had been given DMBA. Based on these findings, it has been concluded that methanolic extract of Rhizophora mucronata leaves (MERML) was safe at both higher and lower dosages and could be assessed for pharmacological study.